2009
DOI: 10.1037/h0100669
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of previously reinforced responding: Research and application.

Abstract: Resurgence describes a procedure, a particular behavioral effect (increases in previously reinforced responding during the extinction of another response), and a behavioral process. There are three phases in a resurgence procedure: reinforcement of a target response, reinforcement of an alternative response, and extinction of both responses. This review examines independent variables in each phase that affect the recurrence (resurgence) of the target response in the third phase as they relate to an understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 36 publications
1
95
1
2
Order By: Relevance
“…In Phase 3, the pigeons were then transitioned to a leaner VI 360-s schedule for the alternative treadle-pressing. The authors found resurgence of target keypecking at low levels during longer interreinforcer intervals of the VI 360-s schedule, which effectively served as local periods of extinction (see Lattal & St. Peter Pipkin, 2009). Along with our study, these findings suggest that resurgence is a function of time without alternative reinforcement, even on relatively brief time scales.…”
Section: Discussionmentioning
confidence: 99%
“…In Phase 3, the pigeons were then transitioned to a leaner VI 360-s schedule for the alternative treadle-pressing. The authors found resurgence of target keypecking at low levels during longer interreinforcer intervals of the VI 360-s schedule, which effectively served as local periods of extinction (see Lattal & St. Peter Pipkin, 2009). Along with our study, these findings suggest that resurgence is a function of time without alternative reinforcement, even on relatively brief time scales.…”
Section: Discussionmentioning
confidence: 99%
“…Many popular behavioral treatments involve alternative reinforcement, such as contingency management for substance abuse (e.g., Higgins et al, 2010; Silverman et al, 2007) and differential reinforcement of alternative behavior (DRA) in individuals with intellectual or developmental disabilities (Petscher, Rey, & Bailey, 2009). Although treatments that use alternative reinforcement are often effective at reducing problem behavior during treatment, the risk of relapse when alternative reinforcement is reduced or removed has led to a recent revival in basic (Lieving & Lattal, 2003; Quick, Pyszczynski, Colston, & Shahan, 2011; Winterbauer & Bouton, 2010) and applied (Volkert, Lerman, Call,& Trosclaire-Lasserre, 2009) research on resurgence (see Lattal & St. Peter Pipkin, 2009, for a review).…”
mentioning
confidence: 99%
“…Resurgence refers to the reoccurrence of a response (i.e., crossovers) that had been replaced by a new response (i.e., stimulus selections) when the new response was no longer reinforced consistently (see Lattal & St. Peter Pipkin, 2007, for a review and Fig. 2 Grey bars indicate the maximum size of the S− in the 20-trial session, as a percentage of the full size, circles show discrimination accuracy, and squares show the percentage of trials with a BcrossoverB discussion of relevance to application).…”
Section: Discussionmentioning
confidence: 99%